214Bi/214Pb radioactivity ratio three-year monitoring in rainwater in Prague - Ambrosino Fabrizio; Thinová Lenka; Hýža Miroslav; Sabbarese Carlo (Nukleonika, 2020)
Continuous monitoring of natural gamma radiation in air has been carried out, during December 2014 – January 2018, with 1-min cyclic measurement in Prague, Czech Republic using a NaI(Tl) probe. The 214Bi/214Pb ratio as a tracer in rainwater has been investigated to study its variations related to both the ambient dose equivalent rate per hour and the amount of rainfall. A hybrid methodology for time series analysis, composed of the aggregation of two signal decomposition methods (multiple linear regression and empirical mode decomposition) and one forecasting method (support vector regression), has been applied to identify the anomalies in the studied signals in order to better find correlations among them. The results show a strong correlation between the ambient dose equivalent rate and the 214Bi/214Pb ratio values and between both these signals and rainfall amount ≥5 mm/h. Furthermore, the considered descendants of radon are mainly responsible for the overall ambient dose equivalent rate.